Il volto crudele del nemico. Figure di terroristi nella letteratura israeliana (Altre Modernità, 2012)
The aim of this lecture is to explore the question of representing terrorists in Israeli literature, namely in the books, Ha-me’ahev, (The Lover), by A.B. Yehoshua, Ha-Qaytanah Shel Kneller (Kneller Happy Camp) by Etgar Keret, Shum gemadim lo yavo’u (The King of Falafel) by Sarah Shilo and Tanin pigua (Croc attack) by Assaf Gavron. A particular attention will be devoted to the confrontation with the other and its purpose in these books.
Keywords: letteratura; Israele; terroristi.